Eudesmanolide sesquiterpenes and protein tyrosine phosphatase 1B inhibitory ent-kaurene diterpenes from aerial parts of Indonesian Wedelia prostata. (June 2017) - Abdjul, Delfly B.; Yamazaki, Hiroyuki; Maarisit, Wilmar; Losung, Fitje; Rotinsulu, Henki; Wewengkang, Defny S.; Sumilat, Deiske A.; Namikoshi, Michio
Graphical abstract: Highlights: Two new (9 R )-eudesman-9, 12-olides were isolated from the Indonesian Wedelia prostata . The structures of the new compounds were elucidated by their NMR spectra. ent -Kaurene diterpenes inhibited the protein tyrosine phosphatase 1B activity. Abstract: Seven eudesmanolide sesquiterpenes (1 –7 ) and two ent -kaurene diterpenes (8 and9 ) including two new (9 R )-eudesman-9, 12-olides, named wedelolides I and J (1 and2 ), were isolated from the aerial parts of Indonesian Wedelia prostata . The structures of1 and2 were assigned based on their spectroscopic data. Diterpenes8 and9 inhibited the activity of protein tyrosine phosphatase 1B (PTP1B) with IC50 values of 8.3 and 28 μM, respectively. Among sesquiterpenes1–7, compound4, wedelolide D, exhibited 32% inhibitory activity against PTP1B at 20 μM.